IMPACT OF DIGITAL TRANSFORMATION ON DISTANCE EDUCATION ADMINISTRATION: A CASE STUDY OF IGNOU JAIPUR REGIONAL OFFICE - Tiwari, Neelu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper analyses the impact of digital transformation on distance education administration, with a focus on the Jaipur Regional Office of Indira Gandhi National Open University (IGNOU). As the inclusion of digital tools and platforms in the education sector is increasing, it is essential to understand how these technological advancements affect the operational processes, accessibility and effectiveness of distance education programmes. Through a case study methodology, this paper examines the strategies adopted by the Jaipur Regional Office of IGNOU to integrate digital technologies in administrative functions, including student registration, course delivery and support services. The research highlights the challenges faced during the transition as well as the benefits achieved, such as improved efficiency, enhanced student engagement and wider access. Additionally, the study identifies key factors that lead to the successful implementation of digital tools in distance education administration. The paper contributes to the growing knowledge field on digital transformation in higher education, providing insights for other institutions to improve policy and practice.